Research on host malcode detection using machine learning - Dong ZHANG; Yao ZHANG; Gang LIU; Gui-xiang SONG (网络与信息安全学报)
Main trends of host malcode detection using machine learning were focused on,and two categories of detection models(namely static analysis and dynamic analysis) were well discussed.Moreover,the critical stages such as malcode samples collection,feature extraction and selection,the construction of machine learning classifiers were considered fully.At last,some future work and challenges in this field were listed.The work can serve as a practical reference for establishing next-generation malcode detection techniques.